The Parry: An Essential Free-Fighting Tool - Peter Hobart; Robert Wolfe (Universidad de León, 2012)
In the arena of free-fighting, traditional blocking techniques and grappling entries often don't work as well as the simple parry. The parry-a refinement of the "slap away" motion that most combatants employ instinctively when confronted with an attack-is a critical tool in the martial artist's armamentarium, yet it has received surprisingly little scrutiny in the research and writing of the arts. Having been students and teachers of various striking and grappling arts for over twenty years, Robert Wolfe and Peter Hobart have pooled their experience to develop a step-by-step approach to understanding and applying the parry in a variety of ways. Part One focuses on the use of the parry primarily in striking engagements; Part Two in the context of grappling.